Injury patterns and incidence in an elite youth football academy: a prospective cohort study of 138 male athletes - Weishorn, Johannes; Jaber, Ayham; Zietzschmann, Severin; Spielmann, Jan; Renkawitz, Tobias; Bangert, Yannic (Journal of Clinical Medicine, 2023)
Background: There is a lack of evidence regarding injury incidence in German elite youth football academies, and the risk of re-injury is unknown. Therefore, the objectives of this study were (1) to determine injury patterns and incidence in an elite youth football academy in Germany, (2) to monitor overuse-/trauma-related injuries over the course of the season, and (3) determine the risk of re-injury. Methods: A prospective cohort study was conducted in the 2012/2013 season among 138 male players from an elite youth football academy in Germany. Injuries were recorded according to the consensus statement on injury definitions and data collection in studies of football injuries. Injury incidence was reported as the number of injuries per 1000 h of exposure and the number of injuries per squad season. Results: A total of 109 injuries were reported, resulting in a cumulative time-loss of 2536 days. A squad of 25 players sustained 19.7 injuries per season, with an average of 23.3 days (15.7-30.9; 95% CI lower-upper) of absence per injury. Ligament sprains (28%), muscle strains (19%) and physeal injuries (12%) were the most common causes of time-loss. Physeal injuries were the most common severe type of injury (29%), with a mean time-loss of 29.7 days (18.2-41.2; 95% CI lower-upper). Re-injuries accounted for 3% of all injuries and resulted in significantly more time-loss than non-re-injuries (60 vs. 23 days; p = 0.01). Conclusion: In the youth academies studied, a team of 25 players sustained an average of 19.7 injuries per season, resulting in a cumulative time-loss of 459 days. Physeal injuries are a major contributor to severe injuries and therefore require special attention.
Gesehen am 20.11.2023